Telepathology and continuous education: important tools for pathologists of developing countries - Barcelo Héctor A; Góngora Jará Hugo (BMC, 2008)
Abstract Education shows that active participation allows the best development of skills to acquire, and the results are better when the information is well documented. Now, with digital images and the Internet, in the case of the Static Telepathology (ST), it is easy to share macroscopic and microscopic photographs. The progress of the technologies enabled a form of Dynamic Telepathology (DT) named "virtual slides", with navigation tools, and can be moved around changing powers as desired, making any personal computer into a digital microscope. The use of these tools in continuous education leads to optimal development of knowledge. We reported the experience of a Latin-American Pathologist from La Rioja, a small Province of Argentina, and we also mentioned the electronic publications in Virtual Hispano-American Congresses of Pathology (VHACP) since 1997(18 reports in the case of ST) and in two Virtual Slide Congress (VSC). In the 1st (2005) and 2nd (2007) Internet VSCs two of our cases were digitized in Spain (case 1 and 3 respectively). In these Virtual Slides, the microscopic images can be moved remotely from any computer connected to the Internet, we should recognize that it will become a valuable continuing Medical Education tool in microscopy, probably related to the phrase "a picture is worth more than a thousand words", then we might add; "what about thousands of images?" Similarly, the autoevaluation test is very important. ST and DT, in support of Virtual Congresses allows learning, teaching and sharing of diseases in scientific presentations and the exchange of views in the forums, these are the optimum material for distance education. In addition we received CDs or DVDs and certificates as authors, recognized by European Institutions. The active participation and the autoevaluation test are the best tools for continuous medical education in telepathology, not only for pathologists in developing countries but for the entire world.